Surface stress waves in a nonhomogeneous elastic half-space. Part I. General results based on spectral analysis. Existence and analyticity theorems - Klecha, T. (Archives of Mechanics, 1996)
Existence of surface waves in a nonhomogeneous elastic half-space is proved on the basis of the stress elastodynamics formulation (cf. [1]). It is demonstrated that in the case when nonhomogeneity depends on depth of the semi-space, both the velocity and amplitude of a surface wave are analytical functions of the wave number.